The role of point‐of‐care platelet function testing in predicting postoperative bleeding following cardiac surgery: a systematic review and meta‐analysis1. (27th April 2015) - Corredor, C.; Wasowicz, M.; Karkouti, K.; Sharma, V.
Summary This systematic review and meta‐analysis appraises the utility of point‐of‐care platelet function tests for predicting blood loss and transfusion requirements in cardiac surgical patients, and analyses whether their use within a transfusion management algorithm is associated with improved patient outcomes. We included 30 observational studies incorporating 3044 patients in the qualitative assessment, and nine randomised controlled trials including 1057 patients in the meta‐analysis. Platelet function tests demonstrated significant variability in their ability to predict blood loss and transfusion requirements. Their use within a blood transfusion algorithm demonstrated a reduction in blood loss at longest follow‐up (mean difference −102.9 ml (95% CI −149.9 to −56.1 ml), p < 0.001), and transfusion of packed red cells (RR 0.86 (95% CI 0.78−0.94), p = 0.001) and fresh frozen plasma (RR 0.42 (95% CI 0.30−0.59), p < 0.001). Viscoelastic methods used in combination with other platelet function tests achieved greater reduction in blood loss (mean difference −111.8 ml (95% CI −174.9 to −49.1 ml), p = 0.0005) compared with their use alone (mean difference −90.6 ml (95% CI 166.1−15.0 ml), p = 0.02). We conclude that incorporation of point‐of‐care platelet function tests into transfusion management algorithms is associated with a reduction in blood loss and transfusion requirements in cardiac surgery patients.